2018
DOI: 10.1016/j.jclepro.2018.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and sensitivity analysis of spiral wound reverse osmosis process for the removal of dimethylphenol from wastewater using 2-D dynamic model

Abstract: Reverse Osmosis (RO) processes are readily used for removing pollutants, such as dimethylphenol from wastewater. A number of operating parameters must be controlled within the process constraints to achieve an efficient removal of such pollutants. Understanding the process dynamics is absolutely essential and is a pre-step for designing any effective controllers for any process. In this work, a detailed distributed two-dimensional dynamic (x and y dimensions and time) model for a spiral-wound RO process is dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…However, applications were initially limited because of intrinsic economic risks associated with the oil production activity and operation constraints related to membrane separations. Nevertheless, the scenario has been changing due to advantages related to the lower energy consumption, low capital investment, low operating costs, and more compact nature of these pieces of equipment [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, applications were initially limited because of intrinsic economic risks associated with the oil production activity and operation constraints related to membrane separations. Nevertheless, the scenario has been changing due to advantages related to the lower energy consumption, low capital investment, low operating costs, and more compact nature of these pieces of equipment [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This in turn has encouraged the employment of different abatement technologies to remove phenol from wastewater such as, steam distillation processes, organic solvent extraction, adsorption, oxidation, and membrane technology to achieve this restriction (Pinto et al, 2005;Busca et al, 2008;Mohammed et al, 2016). Among these technologies, the Reverse Osmosis RO has been recognised as an effective process in wastewater treatment applications regarding the removal of organic compounds from wastewater (Al-Obaidi et al, 2018). Also, the pilot-scale studies using single RO membrane module by Srinivasan et al (2010Srinivasan et al ( , 2011; Sundaramoorthy et al(2011a) have confirmed the feasibility of the RO process for the removal of phenol and phenolic derivatives from wastewater.…”
Section: Introductionmentioning
confidence: 99%